A Novel Antioxidant Protects Against Contrast Medium-Induced Acute Kidney Injury in Rats - Huang, Shuo; Tang, Yanyan; Liu, Tianjun; Zhang, Ning; Yang, Xueyan; Yang, Dingwei; Hong, Ge (Frontiers in Pharmacology, 2020)
Many studies proposed that oxidative stress and apoptosis are key mechanisms in the pathogenesis of contrast-induced AKI (CI-AKI). Xylose-pyrogallol conjugate (XP) is an original effective antioxidant that showed decent antioxidant and anti-apoptosis effect before. Thus the therapeutic effect and mechanism of XP in preventing CI-AKI in the short and long term were investigated in this research. Renal function and histological grade were evaluated to determine the severity of renal injury. Kidney samples were then collected for the measurement of oxidative stress markers and the detection of apoptosis. Transmission electron microscopy (TEM) and western blot of mitochondrial protein were utilized for the analysis of the mitochondrial conditions. The results demonstrated that the CI-AKI rats caused a significant decrease in renal function accompanied by a remarkable increase in MDA, bax, caspase-3, cytochrome c (Cyt C) level, TUNEL positive apoptotic cells, and damaged mitochondria, while a decline in antioxidase activities and mitochondrial superoxide dismutase 2 (SOD2) expression compared with the control rats. However, when XP (50 or 100 or 200 mg/kg/day) was given orally for consecutive 7 days before CI-AKI modeling, XP (200 mg/kg) showed a better capability to restore renal dysfunction, histopathological appearance, the level of apoptosis, mitochondrial damage, oxidative stress, and fibrosis generation without interference in computed tomographic imaging. Our study indicated that antioxidant XP played a nephroprotective role probably through antiapoptotic and antioxidant mechanisms. Besides, XP may regulate the mitochondria pathway via decreasing bax/bcl-2 ratio, inhibiting caspase-3 expression, Cyt C release, and SOD2 activity. Overall, XP as a high-efficient antioxidant may have the potentials to prevent CI-AKI.